Beyond Originative Validity: A Durational Approach to Consent in Marital Annulment Cases - Muhammad Dipbiyansyah Hasanuddin; Muhammad Yassir (UIN Siber Syekh Nurjati Cirebon, 2026)
This article examines the divergence of judicial reasoning in two Religious Court decisions concerning the annulment of marriage in cases involving administrative irregularities and long-term familial relationships. Drawing on the decisions of the Bekasi Religious Court and the Bandung High Religious Court, it argues that the differing outcomes do not arise from variations in applicable legal norms or factual configurations, but from contrasting assumptions regarding the temporality of consent within the structure of marital validity. Adopting a normative-empirical socio-legal approach through the analysis of judicial reasoning, the article develops the concept of continuous affirmation of consent as a socio-legal interpretive framework for understanding how temporality is constructed and operationalized in adjudication. Through this framework, two models of reasoning are conceptualized: an originative model, which fixes validity at the moment of contract formation, and a durational model, which attributes legal relevance to the sustained practice of marital life as an ongoing affirmation of consent. In an anomalous litigation configuration—where the husband, as claimant, denies the existence of the marriage after years of institutionalized family life—temporality emerges as a critical variable for assessing the consistency of claimed consent. The article argues that the durational approach adopted by the first-instance court provides a more context-sensitive reading of marital validity, particularly in accounting for the interaction between legal claims and long-standing relational practices, without displacing the existing normative framework governing annulment. Keywords: Marital Annulment; Temporality of Consent; Socio-Legal Analysis; Litigation Anomaly